PENGARUH PEMBERIAN PUPUK KOMPOS JERAMI PADI DAN PENGATURAN FREKUENSI PENYIRAMAN TERHADAP PERTUMBUHAN DAN PRODUKSI SELADA (Lactuca sativa L.) - Aslamiyah, Nikmatul; Mansyoer, Ariffien; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the interaction between rice straw compost fertilizer application by setting the frequency of watering, as well as determining the best treatment combination for the production of lettuce. The research was conducted in the greenhouse Faculty of Agriculture University of Riau, Pekanbaru on April to June 2013. Research was carried out experimentally using a completely randomized design (CRD) arranged as factorial consisting of 2 factors, 3 replicates and each experimental unit consisted of 3 plants with two plants used as a sample. The first factor is the level of compost dose, namely: (without compost, compost 10 ton/ha, compost 15 ton/ha, compost 20 ton/ha, compost 25 ton/ha, compost 30 ton/ha). As a second factor is the frequency of watering water, namely: (watered 2 times 1 day, watered 1 times 1 day, 1 watered 2 times a day, 1 watered 3 times a day). Data were analyzed statistically by analysis of variance (ANOVA), followed test by Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results showed that the combined treatment of 10 tons / ha of compost with water watering frequency 2 × 1 day deliver the best results for plant fresh weight and leaf area.   Keyword: Lettuce, Rice straw fertilizer compost, Watering frequency